Gaya Bahasa dalam Singir (Syi'ir) Mutiara Isra' Mi'raj sebagai Puisi Jawa Tradisional - Nurianti, Arum Novalia (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2020)
Syi’ir is one of the literary works belonging to traditional Javanese poetry which requires a variety of language styles. Therefore, this research aims to examine (1) the form of language style that is in Syi’ir Mutiara Isra’ Mi’raj and (2) the function of language style that is in Syi’ir Mutiara Isra’ Mi’raj. The theory used is the Keraf language style theory with a stylistic approach from Nurgiyantoro. The data from this research in the form of the lyrics in Syi’ir Mutiara Isra’ Mi’raj . Data collection uses the documentation method in the form of personal documents from informants. The results of this study indicate that there are six dominant language styles and their functions in Syi’ir Mutiara Isra’ Mi’raj including; (1) antonomasia language style with labeling and characteristics function; (2) anaphora language style with emphasis function; (3) assonance language style with sound beauty function; (4) antithesis language style with the function of comparing two opposites; (5) anaculoton language style with the function of concentrating meaning in short language; and (6) enumeration language style with image generating function. Keywords: language style, Singir Mutiara Isra’ Mi’raj, javanese poetry